Fatores associados a qualidade de vida de transgêneros residentes no Estado do Espírito Santo - Coswosck, Kaio Henrique Cesconetto (2022)
The term transgender (TRANS) may be used for people whose gender identity differs from the one assigned at birth. Many of this population segment faces social (lack of social support, discrimination, rejection, transphobia) and psychological (anxiety, depression) challenges. These factors, in turn, may negatively impact the quality of life (QoL) of these individuals. In this context, this study aimed to identify factors associated with QoL of TRANS people. A cross-sectional study with non-probability sample, was conducted with TRANS and cisgender (CIS) adults living in a southeastern Brazilian state. The structured questionnaire was accessed electronically and comprised sociodemographic, health, and QoL information. QoL was assessed through the Short-Form 6 dimensions (SF-6D) instrument, validated for the Brazilian population. Multivariate linear regression analysis (forward method) was applied to determine the influence of independent variables on QoL (outcome variable). All variables that presented p<0.10 in the bivariate analyses were included. The analyses were carried out in the Statistical Package for the Social Sciences (SPSS)® software, version 22.0, with a significance level of 5%. The sample included 65 TRANS individuals and 78 CIS individuals. The CIS group showed a predominance of people with higher education (p=0.002) and higher income (p≤0.001) when compared with the TRANS sample. TRANS participants had worse QoL score (p=0.014) and the same was observed when QoL was assessed by all dimensions (p<0.05). In addition, the place of residence and the report of recent prejudice remained associated with QoL even after adjusting for age, gender identity, occupation, and follow-up by a health professional (p<0.05). In conclusion, the TRANS population showed worse QoL when compared with the CIS population. Being that residing in the capital of the state of Espírito Santo and having suffered episodes of prejudice were the determinants associated with the lower levels of QoL of the TRANS population. Public policies are necessary to promote societal changes that lead to respect for different gender identities and guarantee QOL for these minorities.